2013
DOI: 10.1104/pp.113.222539
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Dependent Protein Kinases: Hubs in Plant Stress Signaling and Development

Abstract: These kinases are identified as integrators in plant signaling, with distinct as well as shared phosphorylation substrates mediating pathway specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
203
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(205 citation statements)
references
References 63 publications
1
203
0
1
Order By: Relevance
“…Although RLKs have been found to be important regulators of root hair growth in Arabidopsis under low-P conditions (Lan et al, 2013), their role seems to be much more general, as they also function in defense and stress responses, including drought, salinity, and cold (Lehti-Shiu et al, 2009;Ye et al, 2009;Das and Pandey, 2010;Marshall et al, 2012;Schulz et al, 2013;Vivek et al, 2013), possibly acting as hubs in stress signaling and development (Das and Pandey, 2010;Asano et al, 2012;Schulz et al, 2013). Several RLKs such as CRPK1 have been shown to play key roles in abiotic stress tolerance, positively or negatively regulating stress tolerance by modulating abscisic acid signaling and reducing the accumulation of reactive oxygen species (Lan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although RLKs have been found to be important regulators of root hair growth in Arabidopsis under low-P conditions (Lan et al, 2013), their role seems to be much more general, as they also function in defense and stress responses, including drought, salinity, and cold (Lehti-Shiu et al, 2009;Ye et al, 2009;Das and Pandey, 2010;Marshall et al, 2012;Schulz et al, 2013;Vivek et al, 2013), possibly acting as hubs in stress signaling and development (Das and Pandey, 2010;Asano et al, 2012;Schulz et al, 2013). Several RLKs such as CRPK1 have been shown to play key roles in abiotic stress tolerance, positively or negatively regulating stress tolerance by modulating abscisic acid signaling and reducing the accumulation of reactive oxygen species (Lan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is in concert with earlier results. According to Schulz et al (2013), CDPKs have a major role in pollen tube growth. Twelve members of the Arabidopsis CDPK gene family are predominantly expressed in pollen (Myers et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous proteomics analysis showed that NbCDPKiso2 was present in the affinity-purified fraction of RCNMV replication complex (29). CDPK is a calcium sensor protein and comprises a multigene family (e.g., 34 members in A. thaliana and 29 members in tomato), which is divided into four subgroups (38)(39)(40). Phylogenetic analysis revealed that NbCDPKiso2 belongs to subgroup II CDPK (Fig.…”
Section: Rcnmv Triggers An Intracellular Ros Burst Via the P27 Replicmentioning
confidence: 99%